PENERAPAN TERAPI BERMAIN MENGAMBAR DEKORATIF TERHADAP PERKEMBANGAN MOTORIK HALUS ANAK USIA 4-5 TAHUN DI WILAYAH BINAAN PUSKESMAS ROWOSARI SEMARANG: THE IMPLEMENTATION OF DECORATIVE PLAYING THERAPY TOWARDS FINE MOTOR DEVELOPMENT OF CHILDREN OF 4-5 YEARS IN THE REGION OF PUSKESMAS ROWOSARI SEMARANG - Badriyatul Hasanah; Novita Wulan sari (SEKOLAH TINGGI ILMU KESEHATAN KESDAM IV DIPONEGORO, 2019)
Fine motor is the child's ability in relation to physical skills involving small muscles, eye, and hand coordination. Decorative drawing is one of the methods that is used to improve children's fine motor skills by decorating images on paper that involve nerve muscle elements, the brain, and the ability of the child's fingers. The purpose of the study is to apply decorative drawing therapy towards the fine motor development of children aged 4-5 years in the region of Puskesmas Rowosari Semarang. This study belongs to descriptive case studies. The subject of this case study used two respondents who had normal fine motor development. Data were collected by observation and measured by Denver II sheet before and after therapy. The results of the case study were found in subject I with normal fine motor development of 70% increasing to a high of 78%, while in subject II with normal fine motor development 73% increased to high by 82%. It is suggested to Puskesmas Rowosari Semarang to use decorative drawings to improve children's fine motor skills as playing therapy in toddler posyandu activities.